A Qualitative Analysis of the Impact of Perceived Corporate Social Responsibility on Employees’ Affective Commitment - Raihène Raho; Houari Benchikh (Business Ethics and Leadership)
Despite the growing interest in corporate social responsibility (CSR) issues, research on micro-CSR remains an emerging field, offering new insights. In this context, this study investigates the perceived effects of different CSR components on employees’ affective organizational commitment, drawing on social exchange theory, social identity theory, and stakeholder theory. The methodology includes a qualitative cross-case and thematic analysis based on a deductive approach using NVivo 14 qualitative data processing software. Data were collected through semi-structured interviews with eight employees from four different sectors operating in the Algerian context. Eleven pre-defined themes were identified in line with the objectives of the study. Based on the analysis of three main themes, the results support the proposition that employees’ perceptions of CSR towards social and non-social stakeholders significantly and positively impact their affective commitment. Employees’ perceptions of CSR towards customers positively impact their affective commitment, although this effect is less pronounced and partially significant. Additionally, employees’ perceptions of CSR towards them have a significant and positive impact on their affective commitment. In addition to the primary findings, the analysis of the interviews revealed that attachment and organizational pride act as mediators, linking perceptions of CSR to employees’ affective commitment. These findings have several implications for current research, highlighting the importance of micro-CSR and revealing the mechanisms involved in individual attitudes within Algerian companies. This could be a valuable strategic tool for strengthening the affective commitment of Algerian employees. Furthermore, the study provides an overview of trends in responsible practices within these companies, with a particular focus on the sectors analyzed in this study.